State Financial Management According to Al-Mawardi and Al-Ghazali - Nahlah Nahlah; Rahman Ambo Masse; Muslimin Kara; Ridwan Markarma (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2022)
This research aims to study the economic thinking of Muslim scholars who lived during the Abbasid dynasty, namely Al-Mawardi, and Al-Ghazali. Where does the state get financial resources according to Al-Mawardi, and what is the theory of money and markets from Al-Ghazali's perspective? The research method is qualitative with a literature study approach that originates from international journals, national journals, websites, and books by Al-Mawardi and Al-Ghazali. The results showed that according to Al-Mawardi, the sources of state finance were obtained through the collection of zakat, Khaimah, fa'i, jizyah, kharaj, public ownership, taxes, and debt. Furthermore, Al-Ghazali's perspective on money is as a medium of exchange in trade. It has "intrinsic" value or value contained in itself, such as gold, silver, or paper used as a medium of exchange. Money is a medium of exchange, a unit of account, a measure of the value of goods, providing social welfare and helping to improve social conditions. Meanwhile, the market in AL-Ghazali's concept is not only a place for transactions between sellers and buyers but also a place of worship and to earn the pleasure of Allah through sharia-compliant trading activities. Tujuan penelitian ini adalah untuk mempelajari pemikiran ekonomi cendekiawan Muslim yang hidup di masa dinasti abbasiyah yaitu Al-Mawardi dan Al-Ghazali. Dari mana negara mendapatkan sumber keuangan menurut Al-Mawardi serta bagaimana teori uang dan pasar dalam perspektif Al-Ghazali.  Metode penelitian adalah kualitatif dengan pendekatan studi literatur yang bersumber pada jurnal internasional, jurnal nasional, website, dan buku baik karya Al-Mawardi maupun karya Al-Ghazali. Hasil penelitian menunjukkan bahwa sumber keuangan negara menurut Al-Mawardi diperoleh melalui pengumpulan zakat, ghanimah, fai’, jizyah, kharaj, kepemilikan umum, pajak, dan utang. Selanjutnya perspketif Al-Ghazali tentang uang adalah sebagai alat tukar dalam perdagangan dan memiliki nilai “intrinsik” atau nilai yang terkandung dalam dirinya sendiri seperti emas, perak, atau kertas yang digunakan sebagai alat tukar. Fungsi uang sebagai alat tukar, satuan hitung, pengukur nilai barang, memberikan kesejahteraan masyarakat, dan membantu memperbaiki kondisi sosial. Sedangkan pasar dalam konsep AL-Ghazali tidak hanya sebagai tempat bertransaksi antara penjual dan pembeli tetapi juga sebagai tempat beribadah dan meraih ridha Allah melalui aktivitas perdagangan yang sesuai syariah.